Synthesis and Characterization of Antitubercular Triazine-Chalcone Hybrid Molecules - Rawat, Aman; Kaur, Atinder; Surjit; Kaur, Harpreet (Asian Journal of Chemistry, 2017)
A new series of 1,3,5-triazine-chalcone hybrid molecules have been synthesized and evaluated in vitro for Mycobacterium tuberculosis H37Rv inhibitory potency using Alamar blue assay and the activity expressed as the minimum inhibitory concentration (MIC) in μg/mL. The antitubercular activity screening data revealed that the compounds 1 and 2B demonstrated comparatively the most potent inhibitory activity, with MIC value 1.6 μg/mL. Most of the compounds displayed significantly promising activity.